2023
DOI: 10.1017/s0954579423000524
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of internalizing symptoms are stable across early adolescence and predicted by executive functions: Longitudinal findings from the Adolescent Brain and Cognitive Development (ABCD) study

Abstract: Early adolescence is characterized by rapid changes in executive function and increased vulnerability to internalizing difficulties. The aim of this study was to explore whether internalizing symptoms are stable across early adolescence and to identify possible links with executive function. Using data from the Adolescent Brain and Cognitive Development Study (ABCD), we identified four dimensions of internalizing symptoms from item-level ratings on the Child Behavior Checklist at ages 10 (n = 10,841) and 12 (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…However, the evidence for an association between cognitive control problems and adolescent mental health problems, is inconsistent. Some studies have shown cross-sectional and prospective associations between cognitive control problems and general vulnerability to psychopathology, as well as with internalizing and externalizing symptomatology specifically, in adolescents (e.g., Romer & Pizzagalli, 2021;Snyder et al, 2019;Vedechkina et al, 2023;White et al, 2017). A recent systematic review similarly concluded that cognitive control problems among young people were associated with both general psychopathology and internalizing and externalizing disorders (Lynch et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence for an association between cognitive control problems and adolescent mental health problems, is inconsistent. Some studies have shown cross-sectional and prospective associations between cognitive control problems and general vulnerability to psychopathology, as well as with internalizing and externalizing symptomatology specifically, in adolescents (e.g., Romer & Pizzagalli, 2021;Snyder et al, 2019;Vedechkina et al, 2023;White et al, 2017). A recent systematic review similarly concluded that cognitive control problems among young people were associated with both general psychopathology and internalizing and externalizing disorders (Lynch et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence for an association between cognitive control problems and adolescent mental health problems, is inconsistent. Some studies have shown cross‐sectional and prospective associations between cognitive control problems and general vulnerability to psychopathology, as well as with internalizing and externalizing symptomatology specifically, in adolescents (e.g., Romer & Pizzagalli, 2021 ; Snyder et al., 2019 ; Vedechkina et al., 2023 ; White et al., 2017 ). A recent systematic review similarly concluded that cognitive control problems among young people were associated with both general psychopathology and internalizing and externalizing disorders (Lynch et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%